Phosphoinositide switches in cell physiology: from molecular mechanisms to disease - Lolicato, Fabio; Nickel, Walter; Haucke, Volker; Ebner, Michael (The journal of biological chemistry, 2024)
Phosphoinositides are amphipathic lipid molecules derived from phosphatidylinositol that represent low abundance components of biological membranes. Rather than serving as mere structural elements of lipid bilayers, they represent molecular switches for a broad range of biological processes, including cell signaling, membrane dynamics and remodeling, and many other functions. Here, we focus on the molecular mechanisms that turn phosphoinositides into molecular switches and how the dysregulation of these processes can lead to disease.